The Correlation between Morphological Awareness and Vocabulary Mastery of the Seventh Semester Students of University of Islam Malang - faiz abdillah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: In learning language, student has different characteristics to understand and has many difficulties in learning language, moreover foreign language. Foreign language learners may face similar difficulties, like understanding the meaning of the word. According to Mofareh (2015) vocabulary knowledge is often viewed as a critical tool for second language learners because a limited vocabulary in a second language impedes successful communication. Linse (2005) states that learners’ vocabulary development is an important aspect of their language development. That is why vocabulary is one of the basic understanding in learning language.This research is done to find out whether there is a significant correlation between morphological awareness and vocabulary mastery of the seventh semester students of English Education Department in University of Islam Malang. This research takes place at English Education Department, with the analysis of product moment. This research focuses on a correlation study between morphological awareness and vocabulary mastery of the seventh semester students of English Education Department.The result of this research presented that there is a correlation. The scores are known from 30 participants (N=30). The research instrument conducted through test; while method in data collection uses distributing test. Technique of analysis data in this research calculating correlation coefficient using Pearson Product Moment in SPSS. The research of this study showed an average of students’ morphological awareness value is 55.33 and average of vocabulary mastery is 78.97. This research has positive correlation because the students has low score in morphological awareness test. Based on the calculating correlation coefficient, this research has very strong correlation because the correlation coefficient is .613. Analysis of data through calculating using Pearson Product Moment by SPSS, the data indicated that the sig (2-tailed) value .000 is lower than level of significant (α) 1% it means that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Based on the result above, the researcher settled that there is a significant correlation between morphological awareness and vocabulary mastery of the seventh semester students of English Education Department.The conclusion of the research shows that there is very low correlation between morphological awareness and vocabulary mastery of the seventh semester students of English Education Department. This research provides some suggestions for (1) students especially the students of English Education Department to develop their morphological awareness; (2) lecturers especially morphology lecturers; and (3) future researchers who want to conduct another research related to this theme can apply this research as a reference and can complete parts which have not covered yet in this research.Keywords: morphological awareness, vocabulary mastery, correlation